2006
DOI: 10.1001/archotol.132.7.729
|View full text |Cite
|
Sign up to set email alerts
|

Association of the FBXO11 Gene With Chronic Otitis Media With Effusion and Recurrent Otitis Media

Abstract: The FBXO11 gene is the human homologue of the gene mutated in the novel deaf mouse mutant jeff (Jf), a single gene model of otitis media. We have evaluated single nucleotide polymorphisms (SNPs) in the FBXO11 gene for association with chronic otitis media with effusion/recurrent otitis media (COME/ROM).Design: A total of 13 SNPs were genotyped across the 98.7 kilobases of genomic DNA encompassing FBXO11. Data were analyzed for single SNP association using generalized estimating equations, and haplotypes were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 26 publications
2
52
2
Order By: Relevance
“…In our study, the FBXO11 association was observed across the spectrum (rAOM/COME) of clinically severe OM. This is broadly concordant with a previously reported association between FBXO11 and recurrent OM/COME in The Minnesota COME/ROM Family Study, 10 although we did not replicate association with the same SNP (rs2134056), which falls outside the haplotype blocks containing our disease-associated SNPs. Conversely, the previous study did not observe an association with rs330787, the most significantly associated SNP observed here, despite the fact that all three cohorts comprise predominantly Caucasian children.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, the FBXO11 association was observed across the spectrum (rAOM/COME) of clinically severe OM. This is broadly concordant with a previously reported association between FBXO11 and recurrent OM/COME in The Minnesota COME/ROM Family Study, 10 although we did not replicate association with the same SNP (rs2134056), which falls outside the haplotype blocks containing our disease-associated SNPs. Conversely, the previous study did not observe an association with rs330787, the most significantly associated SNP observed here, despite the fact that all three cohorts comprise predominantly Caucasian children.…”
Section: Discussionsupporting
confidence: 91%
“…FBXO11/ rs330787 and FBXO11/rs12712997, which are associated in both the primary and replication cohorts, fall in LD block 1. FBXO11/rs2134056, which was associated with COME/ROM in the Minnesota Family Study 10 but was not associated in our study, does not belong to either LD block (r 2 p0.12).…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…Details of recruitment and examination of the study participants have been described previously (Daly et al 1996(Daly et al , 2004Segade et al 2006). Index cases (probands) who had tympanostomy tube surgery for COME/ROM and their family members were recruited for the study.…”
Section: University Of Minnesota (Umn) Studymentioning
confidence: 99%